EFFECT OF LEARNING EVALUATION (ORAL TEST) ON THE LEARNING OUTCOMES OF FEMALE STUDENTS KULLIYYATUL MUBALLIGHAAT AL-ISLAMIYYAH AL-ISHLAH BONDOWOSO SCHOOL YEAR 2020/2021M - Agusyanto; Laila, Nur (Tsaqofah : Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine "Is there an effect of oral exams on the learning outcomes of Kulliyyatul Muballighaat Al-Islamiyyah (KMI) Al-Ishlah Bondowoso students in the 2020/2021 academic year. This study uses a quantitative approach to measure variable X against variable Y, namely whether there is the effect of oral exams on the learning outcomes of Kulliyyatul Muballighaat Al-Islamiyyah (KMI) Al-Ishlah Bondowoso students for the 2020/2021 AD Academic Year (Prsetyo & Jannah, 2011). Based on the results of the research above, the learning evaluation (Oral Test) has a close relationship and has predictive power to the learning outcomes of students at Kulliyyatul Muballighaat Al-Islamiyyah (KMI) Al-Ishlah Bondowoso. Keywords: learning evaluation, oral test